GOFFMAN DRAMATURGY OF MOVEMENT CONCEPT IN SETAN JAWA FILM BY GARIN NUGROHO - Agustina Kusuma Dewi; Yasraf Amir Piliang; Irfansyah Irfansyah; Acep Iwan Saidi (International Journal of Humanity Studies (IJHS), 2020)
DramaturgyGoffmanncloselyrelatedtothemodeloftheinteractionbetweenthepersonabyassumingthatamodeofsocialrelationsasastageshow.Thereareself-raised,therearepurposelyhiddenformanagementtocreateacertainimpression.SetanJawaFilmbyGarinNugroho,asanartfilm,theissueofmovementasthemediasaidthefilmthatmarkstheculturalcodeofJavatointeract.Thisstudyaimstoidentifytheperceptionofmotionapplicabletothe'movement'inSetanJawaFilmusingtestquestionnaireresponsesontheperceptionofrespondentsfromdiverseethnic,whichwaslaterconfirmedbythemethodofFocusedGroupDiscussionwithGoffmannDramaturgyanalysisasthebasisofinterpretation.